2017
DOI: 10.1093/cid/cix056
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Transmission of Drug-resistant HIV in Aruba Resulting in Reduced Susceptibility to the WHO Recommended First-line Regimen in Nearly Half of Newly Diagnosed HIV-infected Patients

Abstract: SummaryThe prevalence of resistant HIV in Aruba has increased to alarming levels, compromising the WHO-recommended first-line regimen. As adequate surveillance as advocated by the WHO is limited, the Caribbean region could face an unidentified rise of NNRTI-resistant HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
2
5
1
1
Order By: Relevance
“…K103N was the most common mutation observed in the linked cases, consistent with a study from Aruba, a highly HIV endemic area in the Caribbean. 51 However, unlike the Aruba cluster, where onward transmission of K103N was observed among ART-naive individuals in a large transmission chain, the pattern of small and independent transmission clusters observed here is more suggestive of multiple transmission events from people with ADR on ART.…”
Section: Discussioncontrasting
confidence: 67%
“…K103N was the most common mutation observed in the linked cases, consistent with a study from Aruba, a highly HIV endemic area in the Caribbean. 51 However, unlike the Aruba cluster, where onward transmission of K103N was observed among ART-naive individuals in a large transmission chain, the pattern of small and independent transmission clusters observed here is more suggestive of multiple transmission events from people with ADR on ART.…”
Section: Discussioncontrasting
confidence: 67%
“…Despite neuropsychiatric side effects [46], ART regimens containing EFV demonstrated sustained antiretroviral activity with continued immunologic recovery in the treatment of naïve HIV patients [478]. The frequency of NNRTI-related mutations E138A and K103N were relatively high in this study, which is similar to the findings of other researchers [48, 49]. K103N is a non-polymorphic major NNRTI resistance mutation that can cause high-level resistance to NVP and EFV.…”
Section: Discussionsupporting
confidence: 86%
“…In developed countries, guidelines recommend baseline genotypic testing in all patients newly diagnosed with HIV infection to ensure the effectiveness of first line ART [6, 7]. Indeed, Hofstra et al demonstrated that in a setting without adequate surveillance, the prevalence of TDRM involving NNRTI resistant HIV can increase to worrisome levels, compromising the efficacy of standard first-line NNRTI-based regimen [8]. Unfortunately, although moderate levels of TDRM have been reported in Brazil [914], ranging from 3.8% in Maranhão [10] to 13.9% in São Paulo [12], the genotyping test is not available for most treatment-naïve patients [15].…”
Section: Introductionmentioning
confidence: 99%